Development and Use of Game-Based Instructional Materials for Teaching Science, Technology, and Society to College Students - Balic, Allan Gregy Villanueva; De Gracia, Rommel Selda (Future Science / FSH-PH Publications, 2024)
This study developed and evaluated game-based instructional ma-terials to enhance learning in the college-level subject, Science, Tech-nology, and Society (STS). Using an action research approach, the study addressed the limitations of traditional teaching methods by introducing the